Iloilo Central Market heritage and business park - Emmanuel, Ronielle P.
The Queen City of the South is constantly rising as one of the most competitive cities in the country. Iloilo City has turned into a ground for various emerging industries wherein investors are constantly finding space to develop. One of the industries that plays a vital role in the city’s economy is the increasing number of Business Process Outsourcing opportunities. A clean and developed environment together with entertainment and cultural activities has provided more than enough reason for more investments and businesses to grow. Celebrations such as the annual Dinagyang Festival has been enticing more guests and tourists to experience the Ilonggo culture. This has led to more preservation projects such as redevelopment of heritage structures to bring the back the old Iloilo in its glory days. The National Historical Commission has already declared the entire Downtown CBD in Iloilo City Proper to be of historical importance and significance to Philippine History. A market building can be found within the CBD and with its current use, the conditions and commercial activity of the facility have been on decline. Its dim and dilapidated environment requires improvements and reformation adapting to a new market typology that shall accommodate business owners and invite the modern consumer. The Iloilo Central Market poses as a site to be redeveloped in this project, showing that it can play a role in preserving the Ilonggo culture as well as contributing to the city’s economy.